Mapping the Evolution of Research Themes on ChatGPT Integration in Education: Thematic and Novelty Keywords - Nabilah, Nabilah; Zafrullah, Zafrullah; Nakamo, Sosteness Jerome; Mwakapemba, Morris Leonard (Elementaria: Journal of Educational Research, 2025)
Abstract. This study aims to examine the evolution and novelty of keywords in the field of ChatGPT in Education using a bibliometric approach. By applying a predefined set of keywords, the researchers identified 310 publications from the Scopus database, which were then analyzed using R Program. The analysis focused on main information, publication trends, keyword evolution over time, and keywords novelty. This analysis concludes that research on ChatGPT in the field of education within the Scopus database began in 2022 and continued through 2025, with the highest surge in publications occurring in 2024, reaching 171 documents. Overall, the findings reveal that the topic of ChatGPT in Education has experienced significant growth, with several core keywords such as "chatgpt", "ai in education", and "artificial intelligence" remaining dominant over the years. Furthermore, the emergence of new keywords such as "efl learners", "contrastive learning", "online learning", "self-directed learning", "technology", "virtual reality", and "attitude" reflects an increasingly diverse research direction, encompassing technological innovations, learning strategies, and psychological dimensions. Keywords marked in bright yellow indicate a high level of novelty and strong potential for further exploration. However, behind AI’s great potential as an educational technology, it is crucial to recognize that not all aspects of education should be fully run by AI. Ethical considerations must remain a central concern, ensuring that the implementation of AI in education maintains a balanced approach between technological functionality and human values.